2018
DOI: 10.5455/jnbs.1519129764
|View full text |Cite
|
Sign up to set email alerts
|

The effect of mobile phone usage on sleep quality in adolescents

Abstract: To evaluate the effect of mobile phone usage on adolescents' sleep quality. This descriptive study took place from January 13-15, 2016 with 9th, 10th, and 11th grade students enrolled at Konya High School (n=380, 51.6% female, age 16.05±0.87). A questionnaire was used for data collection and the Pittsburgh Sleep Quality Index (PSQI) was used to measure the sleep quality of the students. Students received their first mobile phones at an average age of 12.29±1.41). They used their phones 3.03±2.18 hours per day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Currently, a prevalent dual task is the use of smartphone functions while walking or standing. However, smartphone use is associated with sedentary behaviors [ 29 ], injuries [ 30 ] and sleep disorders [ 31 ] and affects the balance ability negatively [ 32 , 33 , 34 ]. In addition, studies showed that smartphone use while maintaining a standing posture increased postural sway [ 35 , 36 ] and might cause changes in the complexity of the center of pressure during some dual-task conditions [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, a prevalent dual task is the use of smartphone functions while walking or standing. However, smartphone use is associated with sedentary behaviors [ 29 ], injuries [ 30 ] and sleep disorders [ 31 ] and affects the balance ability negatively [ 32 , 33 , 34 ]. In addition, studies showed that smartphone use while maintaining a standing posture increased postural sway [ 35 , 36 ] and might cause changes in the complexity of the center of pressure during some dual-task conditions [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Today, the use of smartphones, which include many features, such as music player, video viewing, Internet connection, reading books, and playing games, is increasing day by day among the young people, especially because of being mobile. The studies show that mobile phone is one of the electronic media products that students frequently use in their daily lives 23,24 . In this study, it is seen that more than half of the students prefer mobile phones for playing games.…”
Section: Discussionmentioning
confidence: 59%
“…The studies show that mobile phone is one of the electronic media products that students frequently use in their daily lives. 23,24 In this study, it is seen that more than half of the students prefer mobile phones for playing games.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations